1994
DOI: 10.1111/j.1365-2141.1994.tb05042.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement receptor type 1 (CR1) deficiency on neutrophils in myelodysplastic syndrome

Abstract: We present a patient with myelodysplastic syndromes (MDS) whose neutrophils exhibited defective expression of complement receptor type 1 (CR1). A 73-year-old man was admitted with an evolution of MDS from RA into RAEBT according to the FAB classification of MDS. The neutrophil alkaline phosphatase (NAP) score was zero. The surface expression of membrane effector molecules on neutrophils was determined by indirect immunofluorescence using flow cytometry and monoclonal antibodies. The expression of CR1 on neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…The NAP activity level has no significant correlation to the MPO activity level (7), as confirmed in the current report. A literature review found only two cases of MDS with extremely low NAP activity comparable to the present cases (8,9). The case reported by Ohsaka et al (8) involved absent levels of NAP as well as absent levels of complement receptor type 1, while the expressions of of other complement receptors, Fc receptors and adhesion molecules were normal.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The NAP activity level has no significant correlation to the MPO activity level (7), as confirmed in the current report. A literature review found only two cases of MDS with extremely low NAP activity comparable to the present cases (8,9). The case reported by Ohsaka et al (8) involved absent levels of NAP as well as absent levels of complement receptor type 1, while the expressions of of other complement receptors, Fc receptors and adhesion molecules were normal.…”
Section: Discussionsupporting
confidence: 58%
“…A literature review found only two cases of MDS with extremely low NAP activity comparable to the present cases (8,9). The case reported by Ohsaka et al (8) involved absent levels of NAP as well as absent levels of complement receptor type 1, while the expressions of of other complement receptors, Fc receptors and adhesion molecules were normal. In our series, a flow cytometric evaluation of the PB neutrophils showed no consistent abnormalities in neutrophil cell surface markers, except for a somewhat reduced expression of the Fc γ receptor (CD64) and the G-CSF receptor (CD114) in Case 1 (Table).…”
Section: Discussionsupporting
confidence: 58%
“…¹ release and CR expression on neutrophils are impaired in some MDS patients (Ohsaka et al, 1993a(Ohsaka et al, , 1994. The impairment of adhesion-dependent neutrophil functions may be related to the decreased expression of CD11b/CD18 on MDS neutrophils (Mazzone et al, 1993).…”
Section: Omentioning
confidence: 99%
“…Neutrophil membrane antigens are abnormal with the persistence of an immature myeloid antigen in MDS patients (Baumann et al, 1986). Our previous studies indicated that neutrophil functions, such as superoxide (O 2 ¹ ) release and complement receptor expression, are impaired in some MDS patients (Ohsaka et al, 1993a(Ohsaka et al, , 1994. We also reported that granulocyte colony-stimulating factor (G-CSF) enhances O 2 ¹ release in neutrophils from MDS patients both in vitro and in vivo (Ohsaka et al, 1993a), suggesting that G-CSF administration has merit for enhancing host defence against microorganisms in MDS patients as well as in other haematological disorders (Ohsaka et al, 1989(Ohsaka et al, , 1992(Ohsaka et al, , 1996.…”
mentioning
confidence: 99%
“…Decreased CD10 expression has been associated with increased susceptibility to infections, likely due to its role in neutrophil chemotaxis and coordination of the inflammatory response 22. This becomes clinically evident amongst neonates, patients with burns and those with systemic sepsis, all of which have been shown to have both reduced CD10 expression on their granulocytes, and a degree of immunosuppression 6.…”
Section: Discussionmentioning
confidence: 99%